The Diffusion of Support for Same-Sex Marriage in the US Senate. Issue 4 (6th October 2014) - Theriault, Sean M.; Thomas, Herschel F.
ABSTRACT: Advocates for same-sex marriage have had much to celebrate. The last few years have shown that state after state and senator after senator have declared their support for full marriage equality. Such momentum suggests that their goals will be realized sooner rather than later. In this article, we analyze when senators announce their support for same-sex marriage. Contrary to the popularly held belief that their decisions will quickly snowball into filibuster-proof numbers, we find that most of the easy successes have already been achieved. The difficulty of securing the last few votes may take much longer.